Śmierć poszkodowanych w wypadkach komunikacyjnych a roszczenia z tytułu ubezpieczenia odpowiedzialności cywilnej posiadaczy pojazdów mechanicznych - Kwiecień, Ilona (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
We have very high level of the car accident victims' mortality in Poland. Any damage resulting from driving vehicles could be compensated by insurance company as the motor third party insurance is compulsory. The claims may be made also by parties suffered by death of car accident victim. This article presents the extent of these claims and their influence on insurer's position. The author indicates some problems connected with such claims, like:* difficulties with loss assessment,* specific periods (occurrence policy, injury incubation and long-term pensions),* claims worth increasing in the near owing to:- changes in insurance and law awareness,- changes in the adjudication on loss compensation,- changes in regulation of motor third party insurance according to EU directives (territorial range of cover and the guarantee sum). (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1088, t. 1, s. 342-351